2016
DOI: 10.21776/ub.jitode.2016.004.03.04
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Butterflies in Tourism Diversification Product: Case Study at Coban Rais Waterfall, Batu, East Java

Abstract: The diversity of Butterfly in Coban Rais is one of the potential resources for tourism product diversification and development. The aims of this paper are to determine the magnitude of the butterfly potential as a form of tourism products diversification and development in a sustainable tourism industry. There are 107 species of butterfly that come from six families was found in Coban Rais waterfall. Some species have a very large population in a specified activity, such as mud-puddling and mating. Udara akasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…And yet, Botan Valley has yet to see any significant amount of tourism, despite its enormous potential in terms of butterfly watching. When the literature is examined, butterfly watching is an important tourism activity for its protection and use of nature (Gonzales et al, 2017;Kurnianto et al 2016;Lemelin, 2007;Lemelin & Lopez, 2019). It also has serious economic potential (Gonzales et al, 2017;Laurent, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And yet, Botan Valley has yet to see any significant amount of tourism, despite its enormous potential in terms of butterfly watching. When the literature is examined, butterfly watching is an important tourism activity for its protection and use of nature (Gonzales et al, 2017;Kurnianto et al 2016;Lemelin, 2007;Lemelin & Lopez, 2019). It also has serious economic potential (Gonzales et al, 2017;Laurent, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Gonzalez et al (2017) conducted a study to identify the butterfly species (522 in total) in five tourist trails in Northeast Portugal. Kurnianto et al (2016) identified 107 butterfly species in the vicinity of Indonesia's Shepherd Rais Waterfall. As a result of these studies, tourism destinations have been created for butterfly watching and with ecotourism firmly in mind.…”
Section: Butterfly Watchingmentioning
confidence: 99%
“…Although charismatic species are often the main attractions for ecotourism, tourists are showing increasing interest toward readily-accessible landscapes with greater diversity of plants, birds, herpetofuana, and butterflies, as well as rare, less easily-observed, or less high-profile mammal species (Loubser et al 2001;Lindsay et al 2007;Kurnianto et al 2016;Hausmann 2016). As Chandragiri Hills is a largely intact system with unique landscapes and biodiversity ranging from sub-tropical to the temperate, it has potential for wildlife-based ecotourism.…”
Section: Discussionmentioning
confidence: 99%
“…Among fauna diversity, butterflies might emerge as an alternative to tourist attractions. Butterflies have a tourist attraction due to the beautiful color and shape of their wings as well as different flying patterns (Kurnianto et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several studies on butterfly diversity in waterfall areas have also been conducted in Indonesia. These include the potential of butterflies in tourism diversification products: Case study at Coban Rais Waterfall, Batu, East Java (Kurnianto et al 2016), butterflies in the Rampah Menjangan Waterfall Area, South Hulu District (Noor et al 2016), diversity and abundance of butterflies in the tourist area of Irenggolo Kediri Waterfall (Sulistiyowati and Rahmawati 2018), butterfly inventory (Lepidoptera: Rhopalocera) in two waterfall areas of Padang City (Pratiwi and Dahelmi 2019) and butterflies (Lepidoptera) from Bukit Gatan Waterfall, District of Musi Rawas, South Sumatra Province (Lestari et al 2020).…”
Section: Introductionmentioning
confidence: 99%